Property Insurance and Liability Insurance of Pharmacists and Pharmacies in the Olsztyn Market - Bak, Joanna (Olsztyn Economic Journal, 2013)
This article brings up a very important and current issue concerning the insurance of pharmacists and pharmacies. The aim of the research undertaken was to present the range and factors determining the choice of insurance products for pharmacies and pharmacists operating in Olsztyn. The study is focused on products ensuring protection for the properties owned and used in pharmacies, as well as third-person liability insurance related to the business activity and to the professional practice of a pharmacist. It identifies the most popular insurances in the examined population and specifies the factors determining their choice.